Two new deep-water alpheid shrimps from the Indo-West Pacific (Malacostraca: Decapoda: Caridea) - Arthur Anker (Papéis Avulsos de Zoologia)
Abstract In the present study, two deep-water species of the caridean shrimp family Alpheidae are described from two localities in the Indo-West Pacific, each based on a single specimen. Bannereus kebir sp. nov. is described based on a female holotype collected at a depth of 230-243 m in the Kai Islands, Indonesia. The new species can be easily separated from the two congeners, B. anomalus Bruce, 1988 and B. chani Anker & Pachelle, 2020, by the presence of strap-like epipods on the first to third pereiopods. Salmoneusprofundus sp. nov. is described based on an incomplete hermaphrodite holotype collected at a depth of 218-225 m near Hanover Island, Papua New Guinea. This species differs from all other species of Salmoneus Holthuis, 1955 by the shape and armature of the enlarged minor cheliped, the elongate walking legs, and the absence of a strap-like epipod on the fourth pereiopod. It also represents by far the deepest-known member of Salmoneus, since all other known species in this genus occur at depths shallower than 90 m.